2020
DOI: 10.1186/s12967-020-02437-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular profiling of intrahepatic cholangiocarcinoma in the Chinese population and therapeutic experience

Abstract: Background: The genomic alterations of intrahepatic cholangiocarcinoma (ICC) in the Chinese population have not been fully revealed. Molecular profiling may provide a reference for clinical management, especially targeted therapy. Methods: A retrospective study was conducted in 122 ICC patients. All patients' samples underwent next-generation sequencing (NGS), which analyzed 417 genes. The genetic characteristics, clinical management and therapeutic responses were analyzed. Results: The most commonly mutated g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Regarding VEGF expression, it was found that its overexpression was associated with decreased survival rate though it did not lead to a significant difference. These findings were also in line with those of an Asian study done by Wang et al (Wang et al, 2020). Several factors regulate the occurrence and development of CCA, such as proliferation, apoptosis, and tumor angiogenesis, which are closely related to biological behavior of .…”
Section: Discussionsupporting
confidence: 91%
“…Regarding VEGF expression, it was found that its overexpression was associated with decreased survival rate though it did not lead to a significant difference. These findings were also in line with those of an Asian study done by Wang et al (Wang et al, 2020). Several factors regulate the occurrence and development of CCA, such as proliferation, apoptosis, and tumor angiogenesis, which are closely related to biological behavior of .…”
Section: Discussionsupporting
confidence: 91%
“…Hepatic AS and ICCA also have a TP53 gene mutation associated with reduced survival [ 65 , 66 , 67 ]. In ICCA, mutations are also often observed in the KRAS and ARID1A genes [ 68 , 69 ], the proteins involved in the cell signaling pathways that control cell growth, maturation, and death. Sometimes, mutations occur in genes involved in Wnt signaling, i.e., CTNNB1, AXIN1, and APC [ 70 , 71 ].…”
Section: Comparison Of Liver Cancermentioning
confidence: 99%
“…The goal of molecular research is to develop a tailored therapy protocol based on molecular profiling, in order to minimize toxicity and optimize efficiency. Only recently, Wang et al [ 59 ] published a retrospective study investigating the molecular profile of intrahepatic cholangiocarcinoma in the Chinese population, using next-generation sequencing. The identified genomic alterations were used for personalized therapy and targeted or immunotherapy agents demonstrated superior survival and tumor response outcomes compared to standard chemotherapy[ 59 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Only recently, Wang et al [ 59 ] published a retrospective study investigating the molecular profile of intrahepatic cholangiocarcinoma in the Chinese population, using next-generation sequencing. The identified genomic alterations were used for personalized therapy and targeted or immunotherapy agents demonstrated superior survival and tumor response outcomes compared to standard chemotherapy[ 59 ]. Moreover, genome sequencing and animal model studies suggest that gain-of-function mutations in the IDH gene, could be involved in a subset of cancers with inflammatory signature and trials with IDH inhibitors are ongoing[ 60 ].…”
Section: Future Directionsmentioning
confidence: 99%